RAGAM POLA TABUHAN MUSIK IRINGAN TATUNG DI KOTA SINGKAWANG - Gregorian Imanuel; Imam Ghozali; Chiristianly Yery Silaban (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2021)
AbstractThis research was motivated by the uniqueness of Tatung Accompaniment Music Patterns in Singkawang City. There are wasps accompaniment to Chinese Ethnic Tatung and Dayak Ethnic Tatung. In addition, there are differences in the character of the Chinese Ethnic Tatung wasp pattern and the Dayak Ethnics want to preserve the Tatung culture in Singkawang City. The problem in this research is how the various musical accompaniment patterns of Tatung accompaniment in the City of Singkawang, how the differences in the various patterns of the musical accompaniment of Tatung in the City of Singkawang. The method in this research is descriptive method with a qualitative form of research using musicology. The method in this research is descriptive method with a qualitative form of research using musicology. The results of this study indicate that there are four different wasp accompaniment patterns for Tatung in rituals and Tatung meetings in Singkawang City which perform musical accompaniment rituals and do Tatung when performed. The various accompaniment of Tatung's wasps are Samchienku's beat, Latok Ku's wasps, Ka`Bawakng's wasps, and Ledang's wasps.Keywords: Musical Wasp Patter, Singkawang City, Tatung, Variety